A systematic review of direct oral anticoagulant use in chronic kidney disease and dialysis patients with atrial fibrillation. Issue 2 (2nd March 2018) - Feldberg, Jordanne; Patel, Param; Farrell, Ashley; Sivarajahkumar, Sylvia; Cameron, Karen; Ma, Jennifer; Battistella, Marisa
Abstract: Background: There is a lack of clear benefit and a potential risk of bleeding with direct oral anticoagulant (DOAC) use in chronic kidney disease (CKD) and dialysis patients with atrial fibrillation. The objective of this study was to evaluate how treatment with DOACs affects stroke and bleeding outcomes compared with warfarin or aspirin. Methods: We conducted a systematic review of randomized controlled trials, cohort studies and case series, and searched electronic databases from 1946 to 2017. Studies evaluating stroke and bleeding outcomes with DOAC use in CKD and dialysis patients were included. Results: From 8008 studies, 10 met the inclusion criteria. For moderate CKD patients (estimated glomerular filtration rate  <60 mL/min/1.73 m 2 ), there was no difference in stroke outcomes between dabigatran 110 mg [hazard ratio (HR) 0.78, 95% confidence interval (95% CI) 0.51–1.21], rivaroxaban (HR 0.82–0.84, 95% CI 0.25–2.69) and edoxaban (HR 0.87, 95% CI 0.65–1.18) versus warfarin. Dabigatran (150 mg twice daily) and apixaban reduced risk of stroke or systemic embolism significantly more than warfarin for moderate CKD patients (HR 0.55, 95% CI 0.34–0.89 and HR 0.61, 95% CI 0.39–0.94, respectively). Edoxaban and apixaban were associated with reduced major bleeding events (HR 0.50–0.76) compared with warfarin. Rivaroxaban and dabigatran 110 mg and 150 mg showed no significant difference in major bleeding versus warfarin. In hemodialysis (HD) patients, there was no difference in stroke outcomes between apixaban, dabigatran [relative risk (RR) 1.71, 95% CI 0.97–2.99] or rivaroxaban (RR 1.8, 95% CI 0.89–3.64) versus warfarin. In HD patients, rivaroxaban and dabigatran were associated with an increased major bleeding risk (RR 1.45–1.76), whereas there was no major bleeding difference with apixaban compared to warfarin. Limitations: The heterogeneity of major bleeding and stroke definitions of the 10 included studies. Conclusions: Clinicians should continue to weigh the risk of stroke versus bleeding before prescribing DOACs in the CKD and dialysis population.